Database of fertilization practices on small-scale vegetable farms in Lembang Sub-District, West Java - Pronk, Annette; Vires, Marion de; Adiyoga, Witono; Gunadi, Nikardi; Prathama, Mathias; Merdeka, Agnofi E.; Sugiharto, Joko (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
A database on fertilization practices and farmers' perceptions of livestock manure in 322 horticultural farms in Lembang Sub-District, West Java.